Acidification and warming affect prominent bacteria in two seasonal phytoplankton bloom mesocosms. (24th October 2016) - Bergen, Benjamin; Endres, Sonja; Engel, Anja; Zark, Maren; Dittmar, Thorsten; Sommer, Ulrich; Jürgens, Klaus
Summary: In contrast to clear stimulatory effects of rising temperature, recent studies of the effects of CO2 on planktonic bacteria have reported conflicting results. To better understand the potential impact of predicted climate scenarios on the development and performance of bacterial communities, we performed bifactorial mesocosm experiments (pCO2 and temperature) with Baltic Sea water, during a diatom dominated bloom in autumn and a mixed phytoplankton bloom in summer. The development of bacterial community composition (BCC) followed well‐known algal bloom dynamics. A principal coordinate analysis (PCoA) of bacterial OTUs (operational taxonomic units) revealed that phytoplankton succession and temperature were the major variables structuring the bacterial community whereas the impact of pCO2 was weak. Prokaryotic abundance and carbon production, and organic matter concentration and composition were partly affected by temperature but not by increased pCO2 . However, pCO2 did have significant and potentially direct effects on the relative abundance of several dominant OTUs; in some cases, these effects were accompanied by an antagonistic impact of temperature. Our results suggest the necessity of high‐resolution BCC analyses and statistical analyses at the OTU level to detect the strong impact of CO2 on specific bacterial groups, which in turn might also influence specific organic matter degradation processes.